Limits of Criminalization of False News AsCriminal Acts in Elections - Sukadana, Dewa Ayu Putri (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2024)
The serious danger of election hoaxes is when the hoax is conveyed to the public who are very apathetic or in people who do not trust the current government, and distributed massively ahead of voting day. It is at this stage that hoaxes can intervene free choice of voters who have greater autonomy."The aim of this research is to analyze the basis and limits of criminalization of the act of fabricating and spreading hoaxes election. The focus of this research is on the act of fabricating and disseminating hoaxes part of election crimes. This research is document research using statutory approach and case approach. The results of this research show that the basis The criminalization of the act of fabricating and spreading election hoaxes is not because it exists lies but there are attempts to disrupt the democratic process and there is danger or loss remote harm in the form of a threat to national security. The act of manufacturing and spreading election hoaxes is part of the black campaign. Limitation Criminalization can be carried out if there is a clear and present danger and there is a mistake serious, intentional, from the perpetrator. However, there are difficulties in criminalizing it the act of fabricating and spreading election hoaxes. As part of a black campaign campaign) then the criminal act is formulated as an offense propria and the time of committing the criminal act limited to the campaign period only. The recommendation for this research is the use of facilities other than criminal law must be put forward. There needs to be regulation in the field of administrative law regarding election hoaxes both in election law and information law and electronic transactions.